Formar-se professor no horizonte hermenêutico da psicanálise: a palavra no dizer singular de cada caso - Robaert, Damaris Wehrmann (2024)
The Initial training of a teacher involves several challenges alongside the responsibility of introducing students to the foundational professional studies that will serve as the basis for future educational praxis. With Psychoanalysis integrated into this training, it becomes important to problematize its participation with a view to the repercussions on the professional practice of the teacher. This research, therefore, aimed to think of the relationship of co-determination between the universal professional teaching knowledge that is formed and the singularities of each new concrete case. The central inquiry, therefore, consists of the following question: What are the potentialities and limits of Psychoanalysis in the process of becoming a teacher, as revealed in the dialogical, hermeneutic experience, mediated by challenges and questions from concrete cases of educational praxis with adolescents in a curricular internship of initial teacher training? The main theoretical references, aimed at reflecting on this, were Philosophical Hermeneutics and Psychoanalysis in their relations with Initial Teacher Training and Education. This was a theoretical study linked to a dialogical experience in a Higher Education Licentiate Course, mediated by the singular speech of the trainee-teachers working with adolescents. The dialogical encounter between these three distinct and stimulating horizons—Philosophical Hermeneutics, Psychoanalysis, and Education—revealed the potential for the participation of Psychoanalysis in the process of becoming a teacher, through the singular speech in each case. It encourages the trainee, therefore, to question themselves regarding the universal meaning of the profession, what the educational encounter with the adolescent evokes as a discursive inheritance in each one, to work through it and position themselves with their singular style in the profession to come. As a limitation, I highlight the noticeable reduction in time favorable to open speech, caused by the challenges of concrete cases in educational praxis in relation to psychoanalytic concepts. The time for deep understanding is significantly shortened by the bureaucratization and productivity demands of current formative times, impacted by the ideals of technique and technological predominance. And, in contrast, it is an essential time for the dialogical process in which teacher training takes place, for self-implication in the universal discourse of teaching, integrating it subjectively with a personal style of becoming a teacher.